Versatile Production of Novel PNP Based Metal Complexes Applicable as Water Reduction Catalysts Showing CH/M as Well as CH/π Interactions. Issue 46 (10th November 2020) - Pehn, Richard; Pann, Johann; Ehrmann, Katharina; Viertl, Wolfgang; Roithmeyer, Helena; Bendig, Marvin; Strabler, Christof; Kopacka, Holger; Müller, Thomas; Hofer, Thomas; Brüggeller, Peter
Abstract : Several PNP‐type ligands of the form bis(dianisylphosphanylmethyl)alkylamine, where alkyl is methyl, ethyl, isopropyl, and benzyl (1–4 ), have been coordinated to Co(II), Ni(II), Pd(II), and Pt(II) (5–26 ). This series of water reduction catalysts (WRC) has been characterized by single‐crystal X‐ray structure analysis, multinuclear and 2D NMR spectroscopy, mass spectrometry and a computational study. Intramolecular contact approaches show differences depending on hetero‐ or homoleptic complexes. Both solid state and solution structures indicate an enhancement of steric pressure for the latter. As a consequence CH/M as well as CH/π interactions appear in the X‐ray structures and 1 H NMR spectra. They can also be clearly identified by quantum mechanical calculations on a B3LYP level. Since these WRC contain proton relays due to the used PNP‐ligands, they are prone to proton coupled electron transfer (PCET) during photocatalysis. The different steric pressure influences their reorganisation energy. Obviously, the observed intramolecular contact approaches should be regarded as a tool for the design of future WRC. Abstract : A series of water reduction catalysts is presented showing CH/M and CH/π interactions influencing the photocatalytic activity. These interactions are observable in the solid state as well as in solution. Their dynamic behavior is different in hetero‐ and homoleptic complexes reflecting their catalytic activities. They influence the possibility of proton coupled electron transfer.